PERBANDINGAN PERSENTASE KESALAHAN SENSOR SONAR PENGUKUR JARAK BERBASIS HC-SR04 DAN HY-SRF05 - Estu Broto, Prasepvianto (SAINFIS: Jurnal Sains Fisika, 2024)
A sonar sensor is an ultrasonic sensor that can be used for distance measurement or object detection. The most commonly used types of sonar sensors are HC-SR04 and HY-SRF05 due to their low cost and easy availability. This research aims to determine the error percentage comparison between HC-SR04 and HY-SRF05 sensors. The research is conducted in three stages. The first stage involves hardware design, the second stage involves software design, and the third stage involves testing and data analysis. The data acquisition system for both sonar sensors uses the Arduino Uno microcontroller. The Arduino Uno reads the pulses from both sensors and converts them into distance, which is then displayed on the serial monitor for data analysis purposes. The software design is carried out using the Arduino IDE to program the Arduino Uno. Sensor readings are taken simultaneously every one second. Sensor testing is performed by measuring the distance in 10cm increments from a wall. The sensor will move away from the wall up to a maximum distance of 350cm. Measurements are taken 20 times for each distance, then averaged and the error percentage is calculated. The error percentage obtained from the testing for the HC-SR04 sensor is 1.107579% and for the HY-SRF05 sensor is 3.354425%, both of which fall within the tolerance error percentage below 10%. The results of this research can be used as a reference for using sonar sensors in various applications.